2020
DOI: 10.1038/s41467-020-15797-6
|View full text |Cite|
|
Sign up to set email alerts
|

Record thermopower found in an IrMn-based spintronic stack

Abstract: The Seebeck effect converts thermal gradients into electricity. As an approach to power technologies in the current Internet-of-Things era, on-chip energy harvesting is highly attractive, and to be effective, demands thin film materials with large Seebeck coefficients. In spintronics, the antiferromagnetic metal IrMn has been used as the pinning layer in magnetic tunnel junctions that form building blocks for magnetic random access memories and magnetic sensors. Spin pumping experiments revealed that IrMn Néel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 75 publications
(82 reference statements)
2
28
1
Order By: Relevance
“…6 is associated with the Joule heating of the device by the applied current, and its effect on the AFM state, namely the spin fluctuations of the Mn atoms which are bigger when the device temperature is closer to the Néel temperature. It is worth noting that similar behavior has also been measured in the tunnel anisotropic magnetoresistance of Ir0.2Mn0.8/MgO/Ta magnetic tunnel junctions [55], as well as in the Seebeck coefficient of thin IrMn3 films [56]. In the latter work, the Néel temperature of IrMn3 is measured to be ~ 350 K for a 4 nm thin film, while the Néel temperature for bulk IrMn3 is around 700 K.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…6 is associated with the Joule heating of the device by the applied current, and its effect on the AFM state, namely the spin fluctuations of the Mn atoms which are bigger when the device temperature is closer to the Néel temperature. It is worth noting that similar behavior has also been measured in the tunnel anisotropic magnetoresistance of Ir0.2Mn0.8/MgO/Ta magnetic tunnel junctions [55], as well as in the Seebeck coefficient of thin IrMn3 films [56]. In the latter work, the Néel temperature of IrMn3 is measured to be ~ 350 K for a 4 nm thin film, while the Néel temperature for bulk IrMn3 is around 700 K.…”
Section: Discussionsupporting
confidence: 77%
“…In particular, it is worth noting that Néel temperature reduction as a function of the thickness of IrMn3 has been previously observed. Bulk IrMn3 has a Néel temperature above 700 K [57], which can be reduced to room temperature for thickness values below 3 nm [55,56]. The reduction of the Néel temperature (while still keeping it above room temperature by selecting an appropriate IrMn3 thickness) will be accompanied by a reduction of the exchange constant, which in turn affects the threshold current.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the magnetoresistance sensors that have already been widely used, sub-field researches on novel spin-orbitronic devices are desired for versatile specific IoT applications, including flexible SOT devices for wearable equipment ( Lee et al., 2015 ), SOT-driven antiferromagnetic memories for security and magnetic field-immune applications, as well as spin-orbit THz emitters utilizing the ultrafast spin dynamics and the inverse spin Hall effect (ISHE) in FM/HM bilayers for rapid data communications ( Kampfrath et al., 2013 ; Seifert et al., 2016 ; Wu et al., 2017 ). Besides, spin-orbitronic devices based on MTJs could also harvest the heat dissipation on a chip or from the environment and generate sufficient thermopower by magneto-Seebeck effects ( Liebing et al., 2011 ; Walter et al., 2011 ; Boehnke et al., 2017 ; Tu et al., 2020 ; Friesen et al., 2019 ). In summary, the discovery of SOT-induced electrical manipulation of ferromagnet may be just a beginning and the party of spin-orbit related researches and applications will continue to prosper.…”
Section: Emerging Spin-orbitronic Devices Applicationsmentioning
confidence: 99%
“…The recently observed ftacular temperature dependence of the thermopower in a magnetic heterostructure involving the antiferromagnetic metal IrMn [1] suggests that the spin fluctuations near the antiferromagnetic transition may be responsible for the observed peak at the ordering temperature. This finding is all the more interesting in that the magnetic transition temperature may be tuned by the thickness of the IrMn layers to be at room temperature, which makes the effect highly promising for applications.…”
Section: Introductionmentioning
confidence: 98%
“…A detailed model calculation of the electrical resistivity of antiferromagnetic metals, in the framework of the Self-Consistent Renormalization Theory of spin fluctuations in itinerant magnets [5,6] has been worked out by Ueda [7]. In all these previous studies the anomalies near the transition found for the transport properties appeared to be relatively weak and cannot account for the prominent peak found in the thermopower as a function of temperature or as a function of layer thickness of an IrMn heterostructure [1].…”
Section: Introductionmentioning
confidence: 99%